Electronic Health Record Standards - Kalra, D. (Yearbook of Medical Informatics, 2006)
This paper seeks to provide an overview of the initiatives that are proceeding internationally to develop standards for the exchange of electronic health record (EHR) information between EHR systems.The paper reviews the clinical and ethico-legal requirements and research background on the representation and communication of EHR data, which primarily originates from Europe through a series of EU funded Health Telematics projects over the past thirteen years. The major concepts that underpin the information models and knowledge models are summarised. These provide the requirements and the best evidential basis from which HER communications standards should be developed.The main focus of EHR communications standardisation is presently occurring at a European level, through the Committee for European Normalisation (CEN). The major constructs of the CEN 13606 model are outlined. Complementary activity is taking place in ISO and in HL7, and some of these efforts are also summarised.There is a strong prospect that a generic EHR interoperability standard can be agreed at a European (and hopefully international) level. Parts of the challenge of EHR interoperability cannot yet be standardised, because good solutions to the preservation of clinical meaning across heterogeneous systems remain to be explored. Further research and empirical projects are therefore also needed.
Keywords: Electronic health records; interoperability; standardisation; information model